Alcohol's Effects on the Bystander Decision-Making Model: A Systematic Literature Review - Marcantonio, Tiffany L.; Haikalis, Michelle; Misquith, Chelsea; Leone, Ruschelle M. (The Journal of sex research, 2024)
To decrease rates of sexual assault victimization, young people are encouraged to become involved when they see questionable sexual situations (i.e., be a prosocial bystander). Several factors can facilitate or inhibit intervention, including alcohol use. To inform bystander prevention programs that aim to address alcohol's impact on bystanders, the current study reviewed research focused on alcohol use and bystander decision making. In December 2022, the authors searched published studies from six major electronic databases. Empirical articles were deemed eligible if they examined alcohol and the bystander decision-making model within the context of sexual assault, were based in the United States or Canada, and not an intervention study; 32 studies were included in the final review. Across 32 studies published between 2015-2022, 12 assessed the proximal effects of alcohol on bystander constructs and the additional studies examined the distal effects of alcohol on bystander constructs. Alcohol use appeared to impede earlier steps of the bystander decision-making model; however, alcohol use was associated with impeding and facilitating bystander decision making at the latter half of the model. Overall, alcohol use appears to be negatively rather than positively associated with bystander constructs. Bystander intervention programs may want to move beyond the narrative of alcohol as a risk factor for sexual assault and discuss how alcohol impairs a bystanders' ability to recognize risk. More work is needed to ensure researchers assess alcohol consistently and with similar methods (number of drinks, subjective intoxication) to increase generalizability of findings to prevention programs.